Marginalization of the black male: Insights from the development of the teaching profession (2nd ed.) - Miller, Errol L. (Canoe Press, 1994)
This work seeks to describe the phenomenon of male marginalization in the society by particular reference to the experience of black males in Jamaica, and to explain this phenomenon by the application of a new theory of society; the theory of place. This theory asserts that society is organized on the basis of place (the relative position of individuals and groups with respect to power, resources, status, belief, and culture); that relative inequality is the reality of society, as a consequence of which places in society are scattered between centre and margin; and that at any particular moment in time, therefore, some individuals and groups in society will be more central and others more marginal. The study relates the structure and governance of the primary school system to the place structure and changes over time, in light of challenges from Blacks and responses from the ruling central groups. Data were collected on the institutional provisions for primary schools and teachers' colleges; the gender composition of primary school teachers and principals; and the enrolment, by gender, in teachers' colleges. Some data are also reported on secondary school and university enrolment, by gender, especially when Blacks began to gain access to these institutions in appreciable numbers. Analysis of the data suggests that the marginalization of the black man in the Jamaican educational system has been the result of a complex interaction of social, economic, and political factors operating in the interrelations between different ethnic groups in Jamaican society. Primary school teaching and teacher education shifted from being male dominated to being female dominated in an attempt to limit the upward mobility of black men
Keywords: Sociology of education